2021
DOI: 10.22219/jie.v5i1.14134
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Perbedaan Return Saham Dan Volume Perdagangan Saham Saat Pandemi Dibanding Sebelum Pandemi Covid-19 Di Indonesia

Abstract: This study aims to see and analyze the differences in stock returns and trading volume of shares of transportation companies on the Indonesia Stock Exchange during the pandemic compared to before the Covid-19 pandemic in Indonesia.  This study uses stock prices and stock trading volume on the Indonesia Stock Exchange from November 2019 to July 2020. The data analysis method used was the Kolmogorof Smirnov normality test and the Wilcoxon Signed Rank Test. The research results there is a significant difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Different from Roswaty (2021), Darmayanti et al (2021) and Ameici et al (2021) find that there is a difference in stock returns before and after he announced case the first covid-19 in Indonesia. This study is corroborated by research by Diansari et al (2021)s, which found a substantial difference in stock returns for enterprises in the transportation sector during the Covid-19 pandemic in Indonesia compared to before the pandemic.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Different from Roswaty (2021), Darmayanti et al (2021) and Ameici et al (2021) find that there is a difference in stock returns before and after he announced case the first covid-19 in Indonesia. This study is corroborated by research by Diansari et al (2021)s, which found a substantial difference in stock returns for enterprises in the transportation sector during the Covid-19 pandemic in Indonesia compared to before the pandemic.…”
Section: Introductionsupporting
confidence: 81%
“…Capital market reaction to something incident there is content information can be measured with the use of return as mark change price (Diansari et al, 2021). Decrease and increase request service compared straight with low and high price stock, which also affects decline or increase in stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on stock return conducted by Kefi et al (2020) and Diansari et al (2021) stated that there was a significant difference in stock return between before and during the Covid-19 pandemic. Meanwhile, according to Firdaus & Helty (2021), Darmayanti et al (2020) stated that there was no significant difference in stock return between before and during the Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 93%
“…Informasi adanya pandemik Covid-19 dapat menimbulkan reaksi pasar yang keras terhadap saham-saham perusahaan transportasi yang tercatat di bursa efek Indonesia sehingga menimbulkan kekhawatiran pemegang saham perusahaan terhadap keputusan yang dikeluarkan pemerintah. Hal ini menyebabkan turunnya harga saham, penjualan dan keuntungan bagi perusahaan-perusahaan di industri transportasi bahkan ada yang merugi (Diansari et al, 2021). Menurut Jogiyanto (2013:160), harga saham adalah harga suatu saham yang terjadi di pasar bursa pada saat tertentu yang ditentukan oleh pelaku pasar.…”
Section: Pendahuluanunclassified